Analysis of pulmonary artery variation based on 3D reconstruction of CT angiography - Ma, Xiaochao; Lu, Tianyu; Qin, Da; Cai, Hongfei; Tang, Ze; Yang, Yue; Cui, Youbin; Wang, Rui (Frontiers in Physiology, 2023)
Objective: The purpose of this study is to obtain the pulmonary CT angiographic data for three-dimensional reconstruction, and to analyze the characteristics and variation of the branches of bilateral pulmonary lobes, so as to provide a more intuitive and stereoscopic reference for clinicians in preoperative evaluation. Method: From August 2019 to December 2021, 420 patients in the thoracic surgery department of the first hospital of Jilin University were selected for pulmonary 64 channel contrast enhanced CT examination. Slice thickness is 1.5mm. The obtained DCM documents were analyzed by Mimics 22.0 Software for 3D reconstruction（For example the Figure1 and Figure2）. After reconstruction, the three-dimensional pulmonary artery models were reviewed by chest surgeons and radiologists who were more than attending doctors. At the same time, the two-dimensional image plane, coronary and sagittal plane were used to evaluate the arteries. The characteristics and variations of branches and courses of pulmonary arteries in each lobe of both lungs were analyzed. The subsegmental arterial system was not evaluated. After reconstruction, the three-dimensional model of pulmonary artery was evaluated jointly by chest surgeons and radiologists, and the characteristics and variations of branches and courses of pulmonary artery in each lobe of both lungs were analyzed. Results: There was a large degree of variation in the left superior pulmonary artery in 420 subjects. The blood supply of 4 arteries in the left upper lobe was 50.5% (n = 212), while that of 2 arteries in the left lower lobe was the most, accounting for 79.5% (n = 334). In the variation of right pulmonary artery, the greater variation of right upper lobe pulmonary artery is the branch supply of right upper lobe mediastinal artery, the majority of which are two arteries, accounting for 77.9% of the subjects. Two arteries were the most common, accounting for 64% (n = 269). There may be 2-4 arteries in the right inferior lobe of the lung, mainly 2 arteries, accounting for 79% (n = 332). Conclusion: Three dimensional reconstruction of CT angiography of pulmonary artery can clearly observe the branches and distribution of pulmonary artery, and clarify the variation.